Comparison of alaryngeal voice and speech - Globlek, Dubravka; Stajner-Katusic, Smiljka; Musura, Mušura Horga, Damir; Liker, Marko (2004)
The aim of the research was to compare voice and speech in three groups of alaryngeal speakers: 1. patients using esophageal speech, 2. patients with electroacoustical speech aid and 3. patients with voice prosthesis. Acoustic analysis and pronunciation tests were used for the analysis.
Projekt MZOS
ENG